A three perspective study of the sense of home of nursing home residents: the views of residents, care professionals and relatives. Issue 1 (December 2016) - van Hoof, J.; Verbeek, H.; Janssen, B.; Eijkelenboom, A.; Molony, S.; Felix, E.; Nieboer, K.; Zwerts-Verhelst, E.; Sijstermans, J.; Wouters, E.
Abstract Background The sense of home of nursing home residents is a multifactorial phenomenon which is important for the quality of living. This purpose of this study is to investigate the factors influencing the sense of home of older adults residing in the nursing home from the perspective of residents, relatives and care professionals. Methods A total of 78 participants (n = 24 residents, n = 18 relatives andn = 26 care professionals) from 4 nursing homes in the Netherlands engaged in a qualitative study, in which photography was as a supportive tool for subsequent interviews and focus groups. The data were analyzed based on open ended coding, axial coding and selective coding. Results The sense of home of nursing home residents is influenced by a number of jointly identified factors, including the building and interior design; eating and drinking; autonomy and control; involvement of relatives; engagement with others and activities; quality of care are shared themes. Residents and relatives stressed the importance of having a connection with nature and the outdoors, as well as coping strategies. Relatives and care professionals emphasized the role the organization of facilitation of care played, as well as making residents feel like they still matter. Conclusions The sense of home of nursing home residents is influenced by a multitude of factors related to the psychology of the residents, and the social and built environmental contexts. A holistic understanding of which factors influence the sense of home of residents can lead to strategies to optimize this sense of home. This study also indicated that the nursing home has a dual nature as a place of residence and a place where people are supported through numerous care strategies.